Optimizing the Role of Adolescents as Mosque Administrators Through Improving Digital Marketing Skills - Ida Syafrida; Nurfala Safitri; Nurul Hasanah; Rafli Arsoyo Subiantoro; Muhamad Taufiqurahman; Nadia Mulia (STAI Publisistik Thawalib Jakarta, 2025)
Mosques, as a center of worship for Muslims, have a very strategic function for the community. Collaboration between mosques, educational institutions, the government, and community organizations is also needed to create a solid ecosystem in improving the mental health of Generation Z. This activity contains training that aims to motivate and educate young mosque administrators about the basics of entrepreneurship, ways to promote products, types and forms of promotional content, and the selection of time to upload content on social media. This study uses a mixed method with a qualitative and quantitative descriptive approach. The community service, which was carried out by a team of lecturers and students, was attended by 16 participants who are mosque administrators in the city of Bekasi. In this community service activity, the participants came from various age backgrounds, education levels, and experience managing mosques. Based on the research results obtained from questionnaires completed by community service program participants, the program received a very positive response from respondents. According to most respondents, the training was very relevant and helpful, especially in expanding their understanding of the importance of digital marketing. Most participants mentioned that the training was proper and per their needs as youth in the mosque.